Deconstructing the Common Link Theory: Analysis and Critique in Hadith Studies - Nadia Khairiyah; Luqmanul Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The study of the authenticity of hadith has been a topic of interest including to orientalists. Some of them doubted the authenticity of the traditions on the grounds that the isnad emerged late and many traditions had only one route of transmission hence their historical validity was questionable. In addition, they disagree with the methods of sanad and matan criticism used by hadith scholars in determining the validity of a tradition. The main objective of this study is to understand the approach they use in scientifically analyzing hadith. The method used is to see how the orientalists developed their theories to distinguish between authentic and fabricated traditions. One such theory is the common link theory. This theory was first introduced by Joseph Schacht and further developed by G.H.A. Juynboll. Common link refers to the transmitter who is considered responsible for the transmission of a hadith. However, this theory has been criticized by other orientalists such as Azami, Nabia Abbott, and Sezgin. Juynboll was even considered to be imaginative in developing this theory. In response, he attempted to strengthen his argument by explaining the working principles and logical basis of the theory and comparing it with conventional methods in hadith studies to determine which method is more feasible.